Myocarditis in Admitted Patients with Dengue Fever in a Tertiary Care Hospital of Bangladesh - Noor Mohammed,; Rabiul Alam Md Erfan Uddin,; Muna Islam,; Muhammad Kutubuddin,; Mohammed Mokter Hossain,; Muhammed Syedul Alam,; Mohammed Abdur Rahim,; Indranil Das, (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Severe dengue may be associated with fatal cardiac complications including myocarditis. The incidence of cardiac complications in patients with dengue illness varies greatly from one series to another and there is a paucity of available data on the prevalence of dengue- associated myocarditis in Bangladesh. This study aimed to investigate the occurrence and association of myocarditis in adult patients with dengue in a public tertiary-level hospital in Chattogram, Bangladesh. Materials and methods: A prospective observational study was conducted among 268 admitted patients 18 years of age having confirmed dengue fever at Chittagong Medical College Hospital (CMCH) fromJanuary 2023 to December 2023. Electrocardiography (ECG) cardiac biomarkers, and echocardiography were done for all patients. Diagnosis of myocarditis was as per European Society of Cardiology (ESC) 2013 criteria. Outcome was assessed at in-hospital mortality or discharged. Results: The mean age of 34.6±15.5 years and 66.8% were males. ECG abnormalities were observed in 44 (24%) patients, biomarkers were elevated in 27 (10.1%) patients and 24 (9%) patients had echocardiographic abnormalities. According to ESC 2013 criteria, dengue fever with myocarditis was diagnosed in 40 [14.9% (95% CI: 10.9 19.8%] patients. The patients with myocarditis were more likely to have comorbidity, chest pain and respiratory distress. In-hospital mortality rate was 2.5% and 3.9% in patients with and without myocarditis, respectively (p=0.656). Conclusion: Myocarditis among admitted dengue patients is not uncommon. However, further study is needed to understand its effect on morbidity and mortality among hospitalized dengue patients Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 8-12